Pengaruh Tingkat Upah Minimum dan Inflasi Terhadap Produktivitas Tenaga Kerja di Indonesia Tahun 2014 - 2024 - Jaelani, Fadillah; Hasya, Novira (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
This study aims to analyze the impact of inflation and minimum wage on labor productivity in Indonesia during the period 2014–2024. Productivity is measured by Gross Regional Domestic Product (GRDP) at current prices across provinces. The study employs panel data of 36 provinces with a total of 317 observations, analyzed using the Generalized Least Squares (GLS) method to address issues of autocorrelation and heteroskedasticity. The results show that both inflation and minimum wage have a positive and significant effect on labor productivity. Inflation is significant at the 1% level, while the minimum wage is significant at the 5% level. These findings highlight the importance of price stability and measured minimum wage policies in supporting regional labor productivity growth. The coefficient of determination (R²) is 0.3936, and the F-statistic test shows a probability value of 0.0000 (p < 0.05), indicating that all independent variables collectively have a significant effect on GDP.